Chronic dysimmune demyelinating polyneuropathy: a clinical and electrophysiological study of 93 patients. Issue 1 (July 1996) - Maisonobe, T; Chassande, B; Vérin, M; Jouni, M; Léger, J M; Bouche, P
Abstract : OBJECTIVES–To identify clinical, electrophysiological, and immunological characteristics of chronic immune demyelinating polyneuropathy to define for each group the appropriate therapeutic strategies. METHODS–The clinical and electrophysiological data and the response to treatment of 93 patients with an acquired chronic dysimmune demyelinating polyneuropathy (CDDP) studied over a period of 10 years were reviewed. Two groups were identified: group 1, comprising 64 patients with an idiopathic CDDP, of whom 13 had serum monoclonal or polyclonal gammopathy without detectable antibodies directed against the "myelin associated glycoprotein" (MAG), and group 2, comprising 29 patients with an IgM monoclonal gammopathy of undetermined significance (MGUS) with antibodies binding to the MAG. RESULTS–Group 1 patients had either a progressive or relapsing course. The relapsing course had more pronounced distal slowing of motor conduction velocity. In group 1, there were no significant clinical or electrophysiological differences between patients with or without gammopathy. Patients with anti-MAG antibody (group 2) differed significantly from group 1 patients, especially on the basis of electrophysiological results. They had a more pronounced slowing of peroneal motor nerve conduction velocity, a lower frequency of conduction block, and a distal accentuation of conduction slowing, distinguishing them from those with idiopathic CDDP, Charcot-Marie-Tooth polyneuropathy type 1A, and control subjects. CONCLUSION–The idiopathic CDDP group is heterogeneous with probably different subgroups. Patients with IgM MGUS polyneuropathy and anti-MAG antibodies have characteristics which distinguish them significantly from other CDDP and suggest different immune mechanisms and responses to treatment.